IMPLEMENTATION OF VISUAL METAPHOR-BASED MEDIA ON CELL MATERIAL TOWARD STUDENTS' CRITICAL THINKING SKILLS AND LEARNING MOTIVATION IN GRADE VIII OF SMP NEGERI 6 MAJALENGKA - Atih Novila Windiyani; Anna Fitri Hindriana; Agus Yadi Ismail (FKIP & Sekolah Pascasarjana Universitas Kuningan, 2025)
Students' difficulties in understanding the abstract concept of cells, along with low learning motivation and critical thinking skills, prompted this study. The aim was to examine the implementation of metaphor-based visual learning media on cell material and its effects on the critical thinking skills and learning motivation of 8th-grade students at SMP Negeri 6 Majalengka. The study was conducted from February to April 2025 using a Research and Development (R&D) method with the ADDIE model. A sample of 52 eighthgrade students was selected through proportional random sampling. The media was developed in the form of a video titled